STUDY OF THE NUTRITIONAL BEHAVIOR AS A RISKY HEALTH FACTOR OF ADOLESCENTS FROM DIFFERENT ETHNIC GROUPS IN THE MUNICIPALITY OF PLOVDIV, BULGARIA - Gergana Petrova; Elena Merdzhanova; Valentina Lalova; Penka Angelova; Ralitsa Raycheva; Nikolay Boyadjiev (Peytchinski Publishing, 2022)
Purpose: The present study examines nutritional behavior as a risky health factor for adolescents from different ethnic groups in the Municipality of Plovdiv, Bulgaria. Material and methods: This cross-sectional study was carried out with three different ethnic groups (Bulgarian, Turks, and Roma) in Plovdiv Region in Bulgaria. The study was conducted with a total of 185 middle or high school students. For the purposes of the study original semi-structured questionnaire was developed. Statistical analyses were performed using SPSS Statistics v. 26 software (IBM Corp. Released 2019. Armonk, USA). Results: The daily consumption of meat and fish is highest among boys of Bulgarian origin 10 (19.23%). In the consumption of meat and fish 2-3 times a week, the leading place is occupied by the children of Roma origin. The results of the weekly consumption of milk and dairy products show that 74 (40%) of all respondents consume them every day. Approximately 1/4 of all respondents always add salt to food, and the same share are those who never do that. Conclusion: The results obtained by us do not show large deviations in terms of recommendations for the consumption of meat and fish among the studied groups. Unfortunately, the recommendation made by experts for daily consumption of milk and dairy products is valid for less than half of the studied adolescents, which carries some risk because eating habits and eating behaviors formed in childhood and adolescence are preserved in the future in adulthood.